Simulating the seepage from lined farm canal under shallow water table condition using HYDRUS 2D - Goyal, V.; Jhorar, B.S.; Malik, R.S. (Annals of Agricultural Research, 2014)
The study was conducted in the year 2007-08 to quantify the groundwater recharge dynamics. Experiments were conducted on a 7-year-old cement lined rectangular watercourse and 25-year-old brick lined trapezoidal farm minor. The initial water table was at 2.54 m below soil surface. The height of the bottom of the watercourse (Ho) from the water table was 2.43 m. A finite element flow model, HYDRUS-2D was used to simulate the drawup in observation well pressure heads during recharge from lined watercourses and farm canal under shallow water table condition. The physical flow region involved a soil profile of 200 m wide and 25 m deep with a canal placed at the top. Constant pressure head of 0.37 m and 0.79 m was given on the bottom of the canal for calibration and validation experiments. Saturated hydraulic conductivity was estimated through inverse modeling technique using the experimental pressure heads h time pairs during recharge from the lined watercourses and farm canal. Low Root Mean Square Error (0.1-0.35) and high modeling efficiency (97.9-99.8%) for pressure head during recharge from the lined watercourses calibrated the model successfully. High mean modelling efficiency (99.0 - 99.9%) and low RMSE (0.05-0.36) of predicted and experimental pressure head value validated the HYDRUS 2D model for groundwater recharge from the lined farm canal. The model was used to predict the increase in radial influencing zone with increase in hydraulic conductivity and anisotropy of the surface soil layer. Critical water logging zone increased with increasing hydraulic conductivity and anisotropy of the surface soil layer. The study suggested that HYDRUS 2D may be adopted for simulations in ground water recharge studies.